"Supervision by Public Opinion" or by Government Officials? Media Criticism and Central-Local Government Relations in China. (November 2017) - Chen, Dan
Despite the sophisticated control of media in China, criticism of the party-state is not uncommon. Why does the authoritarian regime allow criticism? This article offers an explanation based on political institutions. It examines central-local government relations and finds that criticism can help advance the interests of different political actors. Criticism of local government bureaus and officials can help the central government ensure local compliance and create favorable public opinion. Local leaders can also use criticism to establish political authority over their subordinates and impress superiors, thus enhancing their chances to advance their career. Despite formal institutional arrangements, both central and local leaders have used informal measures such as criticism to achieve their political objectives. This underscores the importance of informal measures in the operation of China's authoritarian regime.